2020
DOI: 10.3389/fped.2020.00274
|View full text |Cite
|
Sign up to set email alerts
|

CT Coronary Angiography Studies After a Mean Follow-up of 3.8 Years in Children With Kawasaki Disease and Spontaneous Defervescence

Abstract: Background: There is paucity of literature on follow-up of children with Kawasaki disease (KD) who have spontaneous defervescence during the acute stage and do not receive intravenous immunoglobulin. We report herein the role of computed tomography coronary angiography (CTCA) as an imaging modality in such situations. Methods: This prospective observational study was carried out during the period January 2016-June 2017. Children underwent CTCA on 128-slice Dual Source CT (DSCT) scanner (Somatom Definition Flas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Whittaker et al have shown that NT-pro-BNP levels were elevated in 83% patients, while troponins were increased in 68% patients [42]. 2D-echocardiography should be carried out for identification of myocarditis, pericarditis, valvular abnormalities and CAAs [48,56,57]. The electrocardiogram may show changes of myocardial strain.…”
Section: Laboratory Featuresmentioning
confidence: 99%
“…Whittaker et al have shown that NT-pro-BNP levels were elevated in 83% patients, while troponins were increased in 68% patients [42]. 2D-echocardiography should be carried out for identification of myocarditis, pericarditis, valvular abnormalities and CAAs [48,56,57]. The electrocardiogram may show changes of myocardial strain.…”
Section: Laboratory Featuresmentioning
confidence: 99%
“…Reports of long-term observations in patients not receiving IVIG under the judgment of spontaneous defervescence are very limited. Recently, Dusad et al reported that none of the 19 patients with defervesced Kawasaki disease showed any coronary abnormalities 3.8 years after the disease onset ( 25 ). However, future long-term observational studies with a larger number of patients would be necessary before substantial conclusions can be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CTCA is a useful imaging method for delineating coronary artery in KD patients for long term follow-up, especially in older children with thick chest walls and poor acoustic windows ( 21 ). CTCA allows comprehensive evaluation of coronary arteries in children with KD ( 22 ). When KD patients with CAA developed chest tightness, chest pain, shortness of breath, edema, and oliguria, clinicians should seriously suspect that patients may have myocardial infarction, even ECHO results are normal.…”
Section: Discussionmentioning
confidence: 99%